Governance, Risks, and Compliance in Fulfilling the New and Renewable Energy Mix at the State Electricity Company (PLN) - Kurniawan, Kukuh; Sugandi, Yogi Suprayogi; Widianingsih, Ida; Nurasa, Heru (Journal of Ecohumanism, 2024)
This study examines Governance, Risk, and Compliance in the Fulfillment of the New and Renewable Energy Mix in the State Electricity Company (PLN). The problem in this study is the increase in global carbon emissions where the Paris Agreement was subsequently held. As a signatory to the agreement, the Government of Indonesia is committed to reducing greenhouse gas emissions by 2030. GRC (Governance, Risk, Compliance) is a proven way to align technology process strategies and individuals in it, so that governance, risk and compliance in policies can be achieved, especially NRE policies in Indonesia. Furthermore, the research method used in this study is a qualitative research method. The results of the study show that in the aspect of governance, it can be concluded that it is still not good due to various obstacles such as limited private participation, the preparation of solar renewable energy is too rigid, transparency is not ideal, stakeholder participation is still limited, ineffective and efficient due to spending the budget to prepare solar PV auction documents which often fail, are not accountable and have not been able to formulate a strategic vision properly. In the aspect of Risk Management, Operational Risk of readiness for the construction of solar power plants by the auction winner has not been carried out, PLN is still bound by the covenant (World Bank, AFC, IDB, etc.) so that it cannot provide guarantees for the auction winner, and does not have transparency in the process of formulating the RUPTL. Finally, in the aspect of complienence PLN's compliance as the leading solar NRE sector with the government (regulation & fulfillment of obligations), to the international community related to the fulfillment of the net zero target (COP Agreement), the Government/foreign donor institutions for funding assistance to meet the net zero target.